Lymphopenia is associated with late onset Pneumocystis jirovecii pneumonia in solid organ transplantation. Issue 3 (31st March 2018) - Werbel, W.A.; Ison, M.G.; Angarone, M.P.; Yang, A.; Stosor, V.
Abstract: Background: Pneumocystis jirovecii pneumonia ( PJ P) affected 5%‐15% of solid organ transplant (SOT) recipients prior to universal prophylaxis, classically with trimethoprim‐sulfamethoxazole (TMP‐SMX). Guidelines generally recommend 6‐12 months of prophylaxis post‐SOT, yet optimal duration and robust PJ P risk stratification have not been established. Methods: A retrospective, single‐center, case‐control study of PJ P among SOT recipients from January 1998 to December 2013 was conducted. Cases had positive PJ direct fluorescent antibody assay of respiratory specimens. Controls were matched 4:1 by nearest date of SOT. Univariate testing and multivariate logistic regressions were performed. Results: Fifteen cases were identified among 5505 SOT recipients (0.27% rate) and analyzed vs 60 controls. PJ P occurred on average 6.1 years (range 0.9‐13.8) post‐SOT; no case was receiving PJ P prophylaxis at diagnosis. Most were treated with reduced immunosuppression and TMP‐SMX plus steroids (80%). Six patients (40%) required critical care; 3 (20%) died. There were no significant demographic differences, though cases tended to be older at SOT (54 vs 48 years, P  = .1). In univariate analysis, prior viral infection was more common among cases (67% vs 37%, P  = .08). Lower absolute lymphocyte count (ALC) at diagnosis date was strongly associated with PJ P (400 vs 1230 × 10 6  cells/μL, P  < .001); odds of infection were high with ALC ≤ 500 × 10 6 cells (OR 18.7, P  < .01). Conclusion: Pneumocystis jirovecii pneumonia is a rare, late complication of SOT with significant morbidity and mortality. Severe lymphopenia may be useful in identifying SOT recipients who warrant continued or reinstated PJ P prophylaxis.